2019
DOI: 10.1103/physreva.99.013416
|View full text |Cite
|
Sign up to set email alerts
|

Strong dependence of photoionization time delay on energy and angle in the neighborhood of Fano resonances

Abstract: We uncover dramatic variations of the Wigner photoemission time delay with energy and angle in the vicinity of a Fano resonance with the time delay taking opposite signs at different angles at the same energy as well as at the opposite sides of the resonance at the same angle. These variations are illustrated by choosing the Ne 2s → 3p autoionizing state as a case study. Moreover, we demonstrate the existence of strikingly significant changes in time delay due to relativistic effects despite Ne being a low-Z a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This result indicates that the large phase shift difference observed at 10.2 eV in Fig. 2(d) is due to the influence of the resonance at 12.0 eV [32,33] and suggests that future experiments should explore this region in fine detail, to observe the predicted rapid changes in Δη. Both theories reproduce this behavior well, with the time-dependent ab initio method exhibiting excellent agreement, validating the present experimental method.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This result indicates that the large phase shift difference observed at 10.2 eV in Fig. 2(d) is due to the influence of the resonance at 12.0 eV [32,33] and suggests that future experiments should explore this region in fine detail, to observe the predicted rapid changes in Δη. Both theories reproduce this behavior well, with the time-dependent ab initio method exhibiting excellent agreement, validating the present experimental method.…”
Section: Resultsmentioning
confidence: 85%
“…There has been significant theoretical work on the angle-dependent time delay, for example, Refs. [26][27][28][29][30][31][32], but fewer related experimental reports [12,28,33], all using the RABBITT technique. The Wigner delay is theoretically isotropic for single-photon ionization of He, but Heuser et al [28] observed an angular dependence in photoemission delay, attributed to the XUV þ IR two-photon ionization process, inherent in RABBITT interferometry.…”
Section: Introductionmentioning
confidence: 99%
“…Later developments 39 41 provided expressions for the line shapes for decay to the original asymptotic channels, which when added together yield the same profiles as found in the original paper by Fano. Two-channel Fano-like parameterizations have recently been applied to predict the angular dependence of atomic photoionization time delays in the laboratory frame 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Certain specific observations of photoionization delays have however revealed the importance of electron correlation, e.g. delays in the vicinity of Fano resonances [14][15][16] or shakeup satellites [17,18]. The corresponding photoionization delays were however relatively small, typically ranging from a few to less than 50 attoseconds.…”
mentioning
confidence: 99%